Allicin inhibits osteoblast apoptosis and steroid-induced necrosis of femoral head progression by activating the PI3K/AKT pathway. Issue 9 (18th August 2020) - Zhan, Jingdi; Yan, Zijian; Zhao, Mengyao; Qi, Weihui; Lin, Jian; Lin, Zeng; Huang, Yijiang; Pan, Xiaoyun; Xue, Xinghe
Abstract : Steroid-induced avascular necrosis of the femoral head (SANFH) is a major complication of long-term or excessive clinical use of glucocorticoids. Abstract : Steroid-induced avascular necrosis of the femoral head (SANFH) is a major complication of long-term or excessive clinical use of glucocorticoids. Allicin is a classical ingredient extracted from garlic and has many functions such as anti-apoptosis and antibacterial effects. The purpose of this study was to investigate the effect and the mechanism of allicin on apoptosis of osteoblasts induced by dexamethasone (Dex) and SANFH in rats. In vitro, we performed CCK-8, western blotting, TUNEL and other experiments, and the results of these experiments showed that allicin could inhibit the Dex-induced abnormal expression of C-caspase3, C-caspase9, Bax, cytochrome C and Bcl-2 by activating the PI3K/AKT pathway. In vivo, the results of micro-CT, hematoxylin–eosin staining and immunohistochemical analysis suggested that allicin could effectively inhibit the progress of SANFH in rats. In summary, our experiments indicate that allicin is a potential drug for the treatment of SANFH.